Oblikovanje prijetnega vadbenega okolja na osnovi razumevanja teritorialnega vedenja - Sever, Jernej (Šport (Ljubljana), 2019)
Living space can be understood as an area within which the organism meets its basic needs, such as safety, food, a sexual partner and others. When fulfilling of these needs is realistically or sometimes only potentially threatened, the inborn territorial behaviors are usually triggered(Lorenz, 1980). These behaviors are typical for both animals and humans. Hower certain similarities, the perception of living space in animals and humans differs greatly. Human living space is not only related to our biological needs, but is also closely related to our desires and symbolic and imaginary ideas about the world we are living in (Sokolowski, 2008). Misunderstanding of territorial behavior represents an important obstacle in solving social and ecological problems and conflicts of the modern world. Our territorial behavior should therefore be properly cultivated. In sport, we can find an example of good practice that enables the creation of a safe environment, within which an individual can develop his or her potentials and, in the light of ethical principles, expresses and develops combat behavior. Since most of the motor and behavioral skills are developed on the basis of socalled procedural memory (Kandel, 2000), which is recorded in the brain by repetition of movements or procedures, the principles of play in sports, can also be transferred to development of social skills and nature-friendly habits.
Keywords: gamification; gibalne sposobnosti; igrifikacija; motor skills; social skills; socialne veščine; sport; šport; teritorialno vedenje; territorial behavior; training environment; vadbeno okolje